Attachment style of patients diagnosed with psychogenic non-epileptic seizures at a tertiary Epilepsy Center in the Czech Republic - Krámská, Lenka; Hrešková, Lucia; Krámský, David; Vojtěch, Zdeněk (Frontiers in Psychiatry, 2022)
Objective: Quality and type of early relationships with primary caregivers is considered one of the key factors in the etiopathogenesis of many mental disorders including depression, anxiety and conversion disorders. This study focused on the type and quality of attachment style in adult patients with psychogenic non-epileptic seizures (PNES). Method: We evaluated the demographic data and profiles of PNES patients (n=262) and group of healthy volunteers (n=51) measured by the Parental Bonding Inventory (PBI) and Experiences in Close Relationships (ECR) and Experiences in Close Relationships - RS (ECR-RS). Results: Significant differences in measured values between the two groups were identified; specifically, differences in the caregiver style - father and mother overprotection (PBI) was higher in the PNES group. The most frequent type of attachment in PNES was type 2 (preoccupied). Correlations between the PBI and ECR results were also found. Conclusions: This study highlighted certain attachment styles in patients with PNES and statistically significant differences between patients with PNES and a healthy sample. Some correlations between the results of the questionnaires with socio-demographic factors were found. The identification of specific patterns in attachment may be useful for further use in reaching a differential diagnosis and administering tailored psychotherapy of patients with PNES.